Therapeutic Use of Palmitoylethanolamide as an Anti-Inflammatory and Immunomodulator - Maria Clara Inácio de Sá; Marina Gomes Miranda Castor (MDPI AG, 2023)
Palmitoylethanolamine (PEA) is an endocannabinoid-like compound first encountered within the lipid fractions of specific foods and has intrigued researchers since the 1950s due to its therapeutic effects. This survey aims to explore the therapeutic promise held by PEA as an anti-inflammatory and immunomodulatory agent. The therapeutic impact of PEA reverberates across diverse physiological systems, such as the central nervous system, gastrointestinal tract, vascular network, and the digestive and respiratory system. Additionally, it is effective in pain management and reducing inflammation and immune responses. These attributes have fostered collaborations targeting conditions such as Alzheimer's disease, multiple sclerosis, cerebral ischemia, neuroinflammation, general inflammation, pain, coagulopathy, steatohepatitis, and acute lung injury. PEA operates both independently and in synergy with other compounds, like paracetamol, luteolin, and oxymetazoline. This efficacy stems from its interactions with pivotal targets, including PPARα, PPAR-δ, PPAR-γ, CB1, CB2, GPR55, and TRPV1. Additionally, PEA exerts a direct influence on the inflammatory cascade, orchestrating precise adjustments in immune responses. Numerous animal studies have elucidated the inherent potential of PEA. Nevertheless, the imperative of reinforcing clinical investigation is evident. This review notably underscores the pivotal necessity for methodologically rigorous clinical trials to definitively establish the translational efficacy of PEA in ameliorating diverse inflammatory pathologies within the human milieu.